2020
DOI: 10.1021/acsabm.0c00608
|View full text |Cite
|
Sign up to set email alerts
|

Osteoimmunomodulatory Effects of Enamel Matrix Derivate and Strontium Coating Layers: A Short- and Long-Term In Vivo Study

Abstract: Over the past few years, surface modification of implant surfaces has gained substantial attention as a promising solution to avoid the failure of biomaterials after implantation. Although researchers suggest several strategies for surface functionalization of titanium-based implants, only a few studies have compared the osteoimmunomodulatory effects of ionic nanostructures and biofunctionalization in the same biological model. Enamel matrix derivate (EMD) and strontium are both known for their positive influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Optimizing implant surface properties to steer the immune response to an implant has been an area of increasing research focus [ 52 ]. The innate immune response to an implant involves different cells, including neutrophils, dendritic cells, NK cells, and macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Optimizing implant surface properties to steer the immune response to an implant has been an area of increasing research focus [ 52 ]. The innate immune response to an implant involves different cells, including neutrophils, dendritic cells, NK cells, and macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…16 There is a study available, which compares the osteoimmunomodulatory effects of EMD-coated surface with strontium ion-coated implant surface. 17 Compared to EMD-coated surface, strontium-coated surface induced higher bone mineral density, bone surface-to-volume ratio, and bone surface/tissue volume, after 4 weeks of implantation.…”
Section: Introductionmentioning
confidence: 87%
“…In vivo study revealed that EMD-modified implants significantly increased ALP activity and reduced the expression of pro-inflammatory cytokines, suggesting an osteoimmunomodulatory effect of EMD. 176 In another study, a biomimetic glycopeptide hydrogel was designed by Wang et al to mimic the glycoprotein composition and the fibrous structure of a natural extracellular matrix and coated on a PCL/nHA scaffold for bone regeneration. In vitro study revealed that enhanced proliferation and osteogenic differentiation of BMSCs was found on the coated surface, which was further promoted by the M2 macrophage polarization induced by the glycopeptide hydrogel, in vivo study further confirmed the enhanced osteoimmunomodulatory effects of this hybrid scaffold developed here 170 (Fig.…”
Section: Surface Coatings Design Based On Osteoimmune Modulations For...mentioning
confidence: 99%